Supplementary file 2_Consumption of commercial and traditional sugar-sweetened beverages among adolescents in Pakistan: evidence from a national survey.docx - Saima Afaq (614013) (2025)
Background Pakistan faces a growing burden of adolescent overweight, early-onset diabetes, and one of the world’s highest adult diabetes prevalence rates. Yet, nationally representative data on adolescents’ sugar-sweetened beverages (SSBs) consumption are lacking. This study addresses this evidence gap by examining consumption patterns and sociodemographic determinants of SSB intake, including both commercial (packaged) and traditional (home-prepared) drinks, among 10–16-year-olds in Pakistan. Methods We analysed data from the nationally representative TAP (Tobacco & Adolescent Health in Pakistan) survey, conducted from December 2023 to May 2024, including 14,232 adolescents (63% in-school, 37% out-of-school) from nine districts. Weekly frequency of two SSB categories (‘commercial’ (packaged) including soft drinks, fruit drinks, energy drinks; and ‘traditional’ including traditional sweetened home-prepared beverages) was assessed. Consumption was categorised as low, moderate, or high. Weighted descriptive statistics and proportional/generalised ordinal logistic regression were used to examine associations with sociodemographic variables. Results Overall, 70.5% of adolescents reported high total SSB intake (>7 times per week). High consumption was reported in 22.3% for commercial SSBs and 38.1% for traditional SSBs. In adjusted models, males (OR = 1.32, 95% CI: 1.16–1.51), older adolescents (OR = 1.39, 95% CI: 1.20–1.61), and out-of-school youth (OR = 1.48, 95% CI: 1.26–1.74) had greater odds of high total intake, while higher female caregiver’s education was protective (OR = 0.68, 95% CI: 0.54–0.86). Patterns for commercial SSBs were broadly similar, though male caregiver’s education was positively associated. Traditional SSBs also followed these trends, with stronger associations for out-of-school adolescents (OR = 2.05, 95% CI: 1.77–2.37) and rural residence (OR = 1.14, 95% CI: 1.01–1.28). Conclusion SSB consumption including both commercial and traditional beverages is widespread among adolescents in Pakistan. Intake patterns vary significantly by sex, schooling, caregiver education and urbanicity. Policies should prioritise both school and community interventions, implement fiscal and labelling policies, and engage caregivers. Future research should assess portion sizes, nutrient profiles, and strategies to shift social norms around sugar use in beverages.